Collapse of the 2017 Winter Beaufort High: A Response to Thinning Sea Ice?. Issue 6 (26th March 2018) - Moore, G. W. K.; Schweiger, A.; Zhang, J.; Steele, M.
Abstract: The winter Arctic atmosphere is under the influence of two very different circulation systems: extratropical cyclones travel along the primary North Atlantic storm track from Iceland toward the eastern Arctic, while the western Arctic is characterized by a quasi‐stationary region of high pressure known as the Beaufort High. The winter (January through March) of 2017 featured an anomalous reversal of the normally anticyclonic surface winds and sea ice motion in the western Arctic. This reversal can be traced to a collapse of the Beaufort High as the result of the intrusion of low‐pressure systems from the North Atlantic, along the East Siberian Coast, into the Arctic Basin. Thin sea ice as the result of an extremely warm autumn (October through December) of 2016 contributed to the formation of an anomalous thermal low over the Barents Sea that, along with a northward shift of the tropospheric polar vortex, permitted this intrusion. The collapse of the Beaufort High during the winter of 2017 was associated with simultaneous 2‐sigma sea level pressure, surface wind, and sea ice circulation anomalies in the western Arctic. As the Arctic sea ice continues to thin, such reversals may become more common and impact ocean circulation, sea ice, and biology. Plain Language Summary: The warming that the Arctic is currently experiencing has garnered attention in both the popular and scientific press. Indeed, the retreat and thinning of the region's sea ice is one of the most significant and irrefutable indicators of human influence on the climate. In addition to these long‐term trends, the past several years have seen record warmth and extreme events in the region, such as above‐freezing winter temperatures at the North Pole, which may be harbingers of even more dramatic changes in the future. In this paper, we document a recent and previously unknown consequence of this warming: the collapse of the winter Beaufort High that occurred as a result of the intrusion of North Atlantic cyclones into the western Arctic. This phenomenon occurred, for the first time, during the winter of 2017 and resulted in a reversal in surface winds and sea ice motion across the entire western Arctic. We argue that the extreme warmth during the autumn of 2016 resulted in reduced sea ice extent and thickness in the eastern Arctic that persisted into the winter of 2017 allowing extratropical cyclones from the North Atlantic to intrude into the western Arctic. Key Points: The extreme warmth during the autumn of 2016 resulted in reduced sea ice cover in the eastern Arctic that persisted into the winter of 2017 The resulting enhanced air‐sea interaction allowed extratropical cyclones from the North Atlantic to intrude into the western Arctic This leads to the collapse of the Beaufort High resulting in a reversal in surface winds and sea ice motion across the entire western Arctic